Aaron Hill the muses' projector, 1685-1750 - Gerrard, Christine (Oxford University Press, 2003)
Aaron Hill was one of the most lively cultural patrons and brokers on the London literary scene - an image hard to square with the company of undistinguished scribblers to which Pope relegated him in the 'Dunciad'. This biography aims to correct this distorted picture of Hill's life.